Difficulties in the Diagnosis of Giant Abdominopelvic Masses in Women - José Silva Pereira (José de Mello Saúde, 2021)
Massive abdominopelvic masses usually arise from the female reproductive organs. However, these masses may also arise from the gastrointestinal system, urinary system, adjacent soft tissues, peritoneum, retroperitoneum or be metastatic. Differential diagnosis is very important in these huge masses and imaging techniques are usually the best method of assessing, but in some cases, they cannot provide conclusive results and a definitive diagnosis is only achieved after surgical resection. We present three cases of giant abdominopelvic tumors with different etiologies and outcomes. We intend to highlight the importance of early detection, preoperative evaluation, and subsequent surgical management with a multidisciplinary approach to decrease pre and postoperative complications and to improve the quality of live.